Regulation of Financial Assistance - Ferrero Alvarez-Calderón, Guillermo (2015)
This article focuses on the study of a corporate rather, that is a controversial topic: the acquisitions of shares counting on leveraged buyouts. t his has led to increased specialized investment funds, as in Peru, they use these operations to develop their activities. However, the current situation has not been overlooked by the regulation, since this has imposed certain restrictions. After analyzing the phenomenon of leveraged buyouts, the article makes an analysis of the actual regulation to finally provide a possible alternative regulation.